Maternal–Fetal Medicine Workforce Survey: Are We Ready for Regionalized Levels of Maternal Care? - Wenstrom, Katharine D.; D'Alton, Mary E.; O'Keefe, Daniel F. (American Journal of Perinatology, 2018)
Objective To conduct a survey of the members of the Society for Maternal-Fetal Medicine (SMFM) to determine the practice patterns of maternal–fetal medicine (MFM) subspecialists in the United States and to estimate the likelihood that our work force is sufficient to support the proposed MFM staffing requirements for level III and IV maternity centers.Study Design All regular SMFM members in the United States were invited to answer a 26 question survey by email. The survey queried demographic characteristics, practice type, night call arrangements, and whether the respondent's hospital was currently equipped with the services and personnel described in the requirements for level III or IV centers.Results Of the MFM specialists working full time in what would be considered a level III or IV maternity center, only 47.5% took in-house call. Of those taking only call from home or back-up call, the majority reported that during call hours, MFM antepartum and laboring patients are cared for by generalist obstetrician gynecologists; only 6.4% work with MFM hospitalists. Respondents from level III or IV centers also reported that many of their centers did not meet the criteria for nursing support, anesthesia support, or intensive care services.Conclusion These data, if confirmed, indicate that work needs to be done to upgrade services and achieve appropriate staffing to meet the proposed level III and IV criteria for maternity care.
Keywords: maternal–fetal medicine workforce; maternity levels of care